Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

How effective have Canadian national parks been at preventing landscape fragmentation? - Clara E. Freeman-Cole; Jochen A. G. Jaeger (Environmental Monitoring and Assessment, 2026)

Physiological constraints on heat adaptation in birds - Andreas Nord; Marc T. Freeman; Andrew E. McKechnie (Trends in Ecology & Evolution, 2026)

Species‐specific processing of fluorescent dissolved organic matter by Caribbean sponges - Jacqueline G. Keleher; Cole G. Easson; Christopher J. Freeman; Robert W. Thacker; Craig E. Nelson; Alicia M. Reigel; Cara L. Fiore (Limnology and Oceanography, 2026)
Coral reefs are biodiverse and productive ecosystems that are found in typically oligotrophic environments. Many studies have attempted to explain this paradox by demonstrating that microbial symbionts expand metabolic capabilities of host animals. However, few studies have determined if and how coexisting organisms and their symbiotic microbial communities partition available dissolved organic matter. To address this question, we built an artificial reef near the Florida Keys using dominant emergent sponges found in the Caribbean. Fluorescent dissolved organic matter (fDOM) components were measured in incurrent and excurrent water samples of 5–7 biological replicates for each of 10 sponge species. Sponges generally consumed more fDOM as incurrent concentrations increased, but there were also species‐level differences in their responses. We found that microbial abundance (i.e., high and low microbial abundance HMA/LMA classification) explained less variation in fDOM processing than sponge species. Additionally, fDOM analysis revealed both a separation of sponges into two groups based on whether they were net producers or consumers of fDOM, as well as their responses to fDOM concentrations in ambient seawater across species. Differential consumption of fDOM components also yielded species‐specific fluxes of fDOM. This observation contrasts with broad uptake of all fDOM components, which would be expected if net consumption of fDOM was simply concentration dependent and the same for all species. These results provide the first support for species‐level resource partitioning of fluorescent dissolved organic matter across coexisting sponge species and provide additional support for the evolutionary importance of microbial communities in sponges.

Household environmental characteristics influence the house dust metagenome - Isabella Gamez; Farnaz Fouladi; Antonio Gonzalez; James Ward; Ziyue Wang; Laura E. Beane Freeman; Alison Motsinger-Reif; Shyamal D. Peddada; Rob Knight; Mikyeong Lee; Stephanie J. London (Environmental Research, 2026)

High pesticide exposure events and subjective cognitive complaints among US farmers - Yaqun Yuan; Brenda L. Plassman; Shengfang Song; Zhehui Luo; Christine G. Parks; Jonathan N. Hofmann; Laura E. Beane Freeman; Dale P. Sandler; Honglei Chen (Environmental Research, 2026)

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Restoration of ecological interactions: The influence of site and landscape factors - B.A. Woodcock; E. Waddell; M.G. Weites; M. Guy; M. Freeman; K. Park; E. Fuentes-Montemayor; K. Watts; R.J. Barnett; S. l. Rogerson; A. Opris; J. Harris; et al. (Agriculture, Ecosystems & Environment, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

The role of hyperthermia in avian tolerance of hot and humid conditions - Marc T. Freeman; Bianca Coulson; Celiwe A. Ngcamphalala; Mathome O. Makola; Andrew E. McKechnie (Journal of Thermal Biology, 2025)

Integrating multiple data sources with species distribution models to estimate the distribution and abundance of northern bobwhite (Colinus virginianus) in the United States - William B. Lewis; Sprih Harsh; Patrick Freeman; Victoria Nolan; Justin Suraci; Bridgett E. Costanzo; James A. Martin (Ecological Modelling, 2025)

Florida red tides and adverse birth outcomes: Investigating harmful algae as a novel environmental exposure - Rain E. Freeman; Quynh Anh Nguyen; Sandy Haaf; Jason L. Salemi; Catherine M. Bulka (Chemosphere, 2025)

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Carbaryl use and incident cancer in the Agricultural Health Study: an updated analysis - Patricia A. Erickson; Gabriella Andreotti; Richard V. Remigio; Mary H. Ward; Christine G. Parks; Dale P. Sandler; Paul S. Albert; Kathryn Hughes Barry; Jonathan N. Hofmann; Laura E. Beane Freeman (International Journal of Hygiene and Environmental Health, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Metabolic gene expression differences in emaciated and moderately conditioned horses: RNA-seq analysis of postmortem skeletal muscle - M. Parr; E. Shepherd; M. Hines; L. Strickland; T. Freeman; S. Moisa; J. Beever; J. Ivey (Journal of Equine Veterinary Science, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Homing navigation is optimized to diurnal constraints in a tropical seabird, the red-footed booby - Joshua Coste; Stephen C. Votier; Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Peter Carr; Hannah Wood; Alice M. Trevail (Animal Behaviour, 2025)

Whole transcriptome analysis of Mycoplasma bovis-host interactions under in vitro and in vivo conditions - Aga E. Gelgie; Benti D. Gelalcha; Trevor Freeman; Taylor B. Ault-Seay; Jonathan Beever; Oudessa Kerro Dego (Veterinary Microbiology, 2025)

Comparison of the reinforcing, antinociceptive, and respiratory depressant effects of prototypical and G-protein biased mu-opioid receptor agonists in male and female Sprague–Dawley rats - C. Austin Zamarripa; Tanya Pareek; Loc M. Pham; Bruce E. Blough; Hayley M. Schrock; Eric J. Vallender; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2024)

Understanding Marsh Elevation and Accretion Processes and Vulnerability to Rising Sea Levels Across Climatic and Geomorphic Gradients in California, USA - Karen M. Thorne; McKenna L. Bristow; Lyndsay L. Rankin; Katya E. Kovalenko; Justine A. Neville; Chase M. Freeman; Glenn R. Guntenspergen (Estuaries and Coasts, 2024)

Sexually selected differences in warbler plumage are related to a putative inversion on the Z chromosome - Peter O. Dunn; Nicholas D. Sly; Corey R. Freeman‐Gallant; Amberleigh E. Henschen; Christen M. Bossu; Kristen C. Ruegg; Piotr Minias; Linda A. Whittingham (Molecular Ecology, 2024)
Large structural variants in the genome, such as inversions, may play an important role in producing population structure and local adaptation to the environment through suppression of recombination. However, relatively few studies have linked inversions to phenotypic traits that are sexually selected and may play a role in reproductive isolation. Here, we found that geographic differences in the sexually selected plumage of a warbler, the common yellowthroat ( Geothlypis trichas ), are largely due to differences in the Z (sex) chromosome (males are ZZ), which contains at least one putative inversion spanning 40% (31/77 Mb) of its length. The inversions on the Z chromosome vary dramatically east and west of the Appalachian Mountains, which provides evidence of cryptic population structure within the range of the most widespread eastern subspecies ( G. t. trichas ). In an eastern (New York) and western (Wisconsin) population of this subspecies, female prefer different male ornaments; larger black facial masks are preferred in Wisconsin and larger yellow breasts are preferred in New York. The putative inversion also contains genes related to vision, which could influence mating preferences. Thus, structural variants on the Z chromosome are associated with geographic differences in male ornaments and female choice, which may provide a mechanism for maintaining different patterns of sexual selection in spite of gene flow between populations of the same subspecies.

Non-evaporative heat dissipation across the beaks and casques of large forest hornbills - Bianca Coulson; Marc T. Freeman; Juanita Wessels; Andrew E. McKechnie (Journal of Thermal Biology, 2024)

Heat tolerance and evaporative cooling capacity in an arid-zone elephant shrew - Olivia J. B. Chalwin-Milton; Marc T. Freeman; Andrew E. McKechnie (Mammalian Biology, 2024)
Endotherms vary widely in their capacity to defend sublethal body temperature ( T b ) during acute heat exposure. Interspecific variation in the upper thermal limits of small mammals remains poorly studied, particularly in taxa other than bats. We hypothesised that rupicolous elephant shrews (Macroscelidae), on account of their occupancy of above-ground rock crevices in hot habitats and rapid cursorial locomotion, have evolved pronounced heat tolerance capacities. To test this hypothesis, we quantified relationships between T b , resting metabolic rate (RMR) and evaporative water loss (EWL) in western rock elephant shrews ( Elephantulus rupestris ) exposed to air temperature ( T air ) approaching or exceeding T b under conditions of low humidity representative of the study population’s arid, winter-rainfall habitat in western South Africa. Our data revealed a pronounced capacity to tolerate T air > T b , with E. rupestris tolerating T air up to 48.0 ± 0.1 °C while defending T b > 7 °C below T air (maximum T b = 41.64 ± 0.16 °C). Three behavioural pathways were employed to dissipate heat: open mouth panting, flattening their body posture, and nose-licking. At the highest experimental T air values achieved, EWL increased 15.05-fold relative to normothermic levels and heat was dissipated evaporatively at rates equivalent to 174%—240% of metabolic heat production. The heat tolerance limit of T air = 48 °C in E. rupestris is one of the highest yet recorded in a non-volant small mammal, and our data support the notion that elephant shrews possess a pronounced capacity to avoid lethal hyperthermia during acute heat exposure.

Effects of lead on avian thermoregulation in the heat: An experimental test with pied crows (Corvus albus) - Andrew E. McKechnie; Marc T. Freeman; Ryno Kemp; Kerri Wolter; Vinny Naidoo (Environmental Toxicology and Pharmacology, 2024)

Review of skeletal carbonate mineralogy of brachiopods with new material from New Zealand - Abigail M. Smith; David F. Freeman; Ian S. Dixon‐Anderson; Daphne E. Lee (New Zealand Journal of Marine and Freshwater Research, 2024)
We combine published and new mineralogical data on most major taxa of brachiopods from all over the world, to investigate patterns and controls on brachiopod carbonate mineralogy. Measurements of 1726 specimens in 162 species (including 56 fossil species) ranged from 79°N to 74°S and from intertidal to almost 4000 m deep. Calcareous brachiopods mostly create strong resilient valves of very low‐Mg calcite ( = 1.3 wt% MgCO 3 ). The substrate‐cemented Craniida ( = 8.9 wt% MgCO 3 ) and Thecideida ( = 6.5 wt% MgCO 3 ) are unusual in precipitating calcite with higher Mg content. This is the first study to find bimineralic brachiopods; a few species show a combination of low‐Mg ( = 0.8 wt% MgCO 3 ) and intermediate‐Mg calcite ( = 7.2 wt% MgCO 3 ) ( sensu Smith AM, Key MM Jr, Gordon DP. 2006. Skeletal mineralogy of bryozoans: taxonomic and temporal patterns. Earth‐Science Reviews. 78:287–306.). While Mg in calcite varies systematically among valve layers and sometimes along the growth axis, we found no consistent difference between valves of the same individual. A weak latitudinal signal indicates some overall temperature control of Mg, but in general, brachiopods are active calcifiers, precipitating low‐Mg calcite even when Mg:Ca ratio in seawater is high. The drivers on brachiopod mineralogy are individual, environmental, and phylogenetic – resulting in complex variability.

Functional role of metabolic suppression in avian thermoregulation in the heat - Jochen J. Voges; Marc T. Freeman; Blair O. Wolf; Andrew E. McKechnie (Journal of Thermal Biology, 2024)

From route to dive: multi-scale habitat selection in a foraging tropical seabird - Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Julia Ramsden; Alice M. Trevail; Hannah Wood; Stephen C. Votier (Marine Biology, 2024)
Comprehending how environmental variability shapes foraging behaviour across habitats is key to unlocking insights into consumer ecology. Seabirds breeding at high latitudes are exemplars of how marine consumers can adapt their behaviours to make use of predictable foraging opportunities, but prey tends to be less predictable in tropical oceanic ecosystems and may require alternative foraging behaviours. Here we used GPS and time-depth recorder loggers to investigate the foraging behaviour of central placed adult red-footed boobies ( Sula sula rubripes ), a tropical seabird that forages in oceanic waters via diving, or by capturing aerial prey such as flying fish in flight. Dive bout dynamics revealed that red-footed boobies appeared to exploit denser, but more sparsely distributed prey patches when diving further from the colony. Furthermore, although we found no evidence of environmentally driven habitat selection along their foraging routes, red-footed boobies preferentially dived in areas with higher sea surface temperatures and chlorophyll-a concentrations compared to conditions along their foraging tracks. This multi-scale variation implies that habitat selection differs between foraging routes compared to dive locations. Finally, red-footed booby dives were deepest during the middle of the day when light penetration was greatest. Ultimately, we highlight the importance of gaining insights into consumer foraging across different ecosystems, thereby broadening understanding of how animals might respond to changing environmental conditions.

Decomposition rates appear stable despite elevated shrimp abundances following hurricanes in montane streams, Puerto Rico - Max Kelly; Mary Freeman; Pablo E. Gutiérrez-Fonseca; Jesús E. Gómez; Rafael Pérez; Lulu Victoria-Lacy; Alonso Ramírez; Catherine Pringle (Hydrobiologia, 2024)

Textile dyes as a source of groundwater contamination in Mandalay, Myanmar - Surya M. Freeman; Chit Wityi Oo; Melissa E. Lenczewski; Moe Myint Kyaw (Hydrogeology Journal, 2024)

Pesticide use and inflammatory bowel disease in licensed pesticide applicators and spouses in the Agricultural Health Study - Dazhe Chen; Christine G. Parks; Jonathan N. Hofmann; Laura E. Beane Freeman; Dale P. Sandler (Environmental Research, 2024)

Benign breast disease and breast cancer risk in African women: a case–control study - Olasubomi J. Omoleye; Jincong Q. Freeman; Mojisola Oluwasanu; Adenike Adeniji-Sofoluwe; Anna E. Woodard; Benjamin S. Aribisala; Prisca O. Adejumo; Atara Ntekim; Timothy Makumbi; Paul Ndom; IkeOluwapo O. Ajayi; Olufunmilayo I. Olopade; et al. (Cancer Causes & Control, 2024)

Evolution of avian heat tolerance: The role of atmospheric humidity - Marc T. Freeman; Bianca Coulson; James C. Short; Celiwe A. Ngcamphalala; Mathome O. Makola; Andrew E. McKechnie (Ecology, 2024)
The role of atmospheric humidity in the evolution of endotherms' thermoregulatory performance remains largely unexplored, despite the fact that elevated humidity is known to impede evaporative cooling capacity. Using a phylogenetically informed comparative framework, we tested the hypothesis that pronounced hyperthermia tolerance among birds occupying humid lowlands evolved to reduce the impact of humidity‐impeded scope for evaporative heat dissipation by comparing heat tolerance limits (HTLs; maximum tolerable air temperature), maximum body temperatures ( T b max), and associated thermoregulatory variables in humid (19.2 g H 2 O m −3 ) versus dry (1.1 g H 2 O m −3 ) air among 30 species from three climatically distinct sites (arid, mesic montane, and humid lowland). Humidity‐associated decreases in evaporative water loss and resting metabolic rate were 27%–38% and 21%–27%, respectively, and did not differ significantly between sites. Decreases in HTLs were significantly larger among arid‐zone (mean ± SD = 3.13 ± 1.12°C) and montane species (2.44 ± 1.0°C) compared to lowland species (1.23 ± 1.34°C), with more pronounced hyperthermia among lowland ( T b max = 46.26 ± 0.48°C) and montane birds ( T b max = 46.19 ± 0.92°C) compared to arid‐zone species (45.23 ± 0.24°C). Our findings reveal a functional link between facultative hyperthermia and humidity‐related constraints on evaporative cooling, providing novel insights into how hygric and thermal environments interact to constrain avian performance during hot weather. Moreover, the macrophysiological patterns we report provide further support for the concept of a continuum from thermal specialization to thermal generalization among endotherms, with adaptive variation in body temperature correlated with prevailing climatic conditions.

Occupational farm work activities influence workers’ indoor home microbiome - Kathryn R. Dalton; Mikyeong Lee; Ziyue Wang; Shanshan Zhao; Christine G. Parks; Laura E. Beane-Freeman; Alison A. Motsinger-Reif; Stephanie J. London (Environmental Research, 2024)

Contingent administration of typical and biased kappa opioid agonists reduces cocaine and oxycodone choice in a drug vs. food choice procedure in male rhesus monkeys - C. Austin Zamarripa; Sally L. Huskinson; E. Andrew Townsend; Thomas E. Prisinzano; Bruce E. Blough; James K. Rowlett; Kevin B. Freeman (Psychopharmacology, 2024)

Joint associations between established genetic susceptibility loci, pesticide exposures, and risk of prostate cancer - Lauren M. Hurwitz; Laura E. Beane Freeman; Gabriella Andreotti; Jonathan N. Hofmann; Christine G. Parks; Dale P. Sandler; Jay H. Lubin; Jia Liu; Kristine Jones; Sonja I. Berndt; Stella Koutros (Environmental Research, 2023)

Exposure to pesticides and risk of Hodgkin lymphoma in an international consortium of agricultural cohorts (AGRICOH) - Joanne Kim; Maria E. Leon; Leah H. Schinasi; Isabelle Baldi; Pierre Lebailly; Laura E. Beane Freeman; Karl-Christian Nordby; Gilles Ferro; Alain Monnereau; Maartje Brouwer; Kristina Kjaerheim; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2023)
Purpose Some pesticides may increase the risk of certain lymphoid malignancies, but few studies have examined Hodgkin lymphoma (HL). In this exploratory study, we examined associations between agricultural use of 22 individual active ingredients and 13 chemical groups and HL incidence. Methods We used data from three agricultural cohorts participating in the AGRICOH consortium: the French Agriculture and Cancer Cohort (2005–2009), Cancer in the Norwegian Agricultural Population (1993–2011), and the US Agricultural Health Study (1993–2011). Lifetime pesticide use was estimated from crop-exposure matrices or self-report. Cohort-specific covariate-adjusted overall and age-specific (< 40 or ≥ 40 years) hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression and combined using random effects meta-analysis. Results Among 316 270 farmers (75% male) accumulating 3 574 815 person-years at risk, 91 incident cases of HL occurred. We did not observe statistically significant associations for any of the active ingredients or chemical groups studied. The highest risks of HL overall were observed for the pyrethroids deltamethrin (meta-HR = 1.86, 95% CI 0.76–4.52) and esfenvalerate (1.86, 0.78–4.43), and inverse associations of similar magnitude were observed for parathion and glyphosate. Risk of HL at ≥ 40 years of age was highest for ever-use of dicamba (2.04, 0.93–4.50) and lowest for glyphosate (0.46, 0.20–1.07). Conclusion We report the largest prospective investigation of these associations. Nonetheless, low statistical power, a mixture of histological subtypes and a lack of information on tumour EBV status complicate the interpretability of the results. Most HL cases occurred at older ages, thus we could not explore associations with adolescent or young adult HL. Furthermore, estimates may be attenuated due to non-differential exposure misclassification. Future work should aim to extend follow-up and refine both exposure and outcome classification.

Impact of organic carbon reworking upon GDGT temperature proxies during the Paleocene-Eocene Thermal Maximum - Gordon N. Inglis; Pablo Martínez-Sosa; Jessica E. Tierney; Caitlyn R. Witkowski; Shelby Lyons; Allison A. Baczynski; Katherine H. Freeman (Organic Geochemistry, 2023)

Correction to: Microglial MHC‑I induction with aging and Alzheimer’s is conserved in mouse models and humans - Collyn M. Kellogg; Kevin Pham; Adeline H. Machalinski; Hunter L. Porter; Harris E. Blankenship; Kyla B. Tooley; Michael B. Stout; Heather C. Rice; Amanda L. Sharpe; Michael J. Beckstead; Ana J. Chucair‑Elliott; Sarah R. Ocañas; et al. (GeroScience, 2023)

A new approach methodology using kinetically-derived maximum dose levels in risk assessment – A case study with afidopyropen - Anne E. Loccisano; Elaine Freeman; Adriana Doi; Markus Frericks; Ivana Fegert; Eric Fabian; Brandy Riffle (Regulatory Toxicology and Pharmacology, 2023)

Microglial MHC-I induction with aging and Alzheimer’s is conserved in mouse models and humans - Collyn M. Kellogg; Kevin Pham; Adeline H. Machalinski; Hunter L. Porter; Harris E. Blankenship; Kyla B. Tooley; Michael B. Stout; Heather C. Rice; Amanda L. Sharpe; Michael J. Beckstead; Ana J. Chucair-Elliott; Sarah R. Ocañas; et al. (GeroScience, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

DISCOVR strain pipeline screening – Part I: Maximum specific growth rate as a function of temperature and salinity for 38 candidate microalgae for biofuels production - Michael Huesemann; Scott Edmundson; Song Gao; Sangeeta Negi; Taraka Dale; Andrew Gutknecht; Hajnalka E. Daligault; Carol K. Carr; Jacob Freeman; Theresa Kern; Shawn R. Starkenburg; Cheryl D. Gleasner; et al. (Algal Research, 2023)

Air pollution and the onset of balance problems: The Canadian longitudinal study on aging - Alyssa Grant; Marie-Jeanne Kergoat; Ellen E. Freeman (International Journal of Hygiene and Environmental Health, 2023)

Seasonal variability in macroinvertebrate assemblages in paired perennial and intermittent streams in Costa Rica - Darixa D. Hernández-Abrams; Scott Connelly; Mary C. Freeman; Pablo E. Gutiérrez-Fonseca; Seth J. Wenger (Hydrobiologia, 2023)

Host phylogeny and elevation predict infection by avian haemosporidians in a diverse New Guinean bird community - Geoffrey C. F. Lau; Alexandra M. Class Freeman; Paulo Pulgarín‐R; Carlos Daniel Cadena; Robert E. Ricklefs; Benjamin G. Freeman (Journal of Biogeography, 2023)
Aim The biotic interactions hypothesis predicts that interactions between species are stronger at lower elevations compared to higher elevations. We tested whether this prediction is met by examining elevational patterns in avian haemosporidian infections in New Guinean birds. Location YUS Conservation Area, Papua New Guinea. Taxon Birds and haemosporidia. Methods We collected blood samples from 2268 individuals of 66 bird species along a reef‐to‐ridgetop tropical elevational gradient covering ~3000 m of elevation. We used molecular methods to screen samples for haemosporidian parasites, and sequenced 70% of positive infections to determine the identity of parasite genera. We fit a phylogenetic generalized mixed‐effects model to test whether infection prevalence was higher at low elevations, as predicted by the biotic interactions hypothesis. Finally, we tested for phylogenetic signal in parasite prevalence and in host elevational distribution using Pagel's λ . Results Overall parasite prevalence was 45% . Infection prevalence decreased with elevation, though prevalence remained above ~30% even for high‐elevation communities between 2000 and 3000 m. We found strong phylogenetic signal in infection prevalence, but no phylogenetic signal in host elevational distribution. Nearly all sequenced infections (97%) were of Haemoproteus. Main Conclusions Our results are consistent with predictions arising from the biotic interactions hypothesis. However, phylogenetic relationships among hosts are a much better predictor of infection prevalence than is elevational position: closely related bird species tend to have similar infection prevalence regardless of the elevations where they live.

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

Monitoring extinction risk and threats of the world’s fishes based on the Sampled Red List Index - Rafael Miranda; Imanol Miqueleiz; William Darwall; Catherine Sayer; Nicholas K. Dulvy; Kent E. Carpenter; Beth Polidoro; Nadia Dewhurst-Richman; Caroline Pollock; Craig Hilton-Taylor; Robin Freeman; Ben Collen; et al. (Reviews in Fish Biology and Fisheries, 2022)
Global biodiversitytargets require us to identify species at risk of extinction and quantify status and trends of biodiversity. The Red List Index (RLI) tracks trends in the conservation status of entire species groups over time by monitoring changes in categories assigned to species. Here, we calculate this index for the world’s fishes in 2010, using a sampled approach to the RLI based on a randomly selected sample of 1,500 species, and also present RLI splits for freshwater and marine systems separately. We further compare specific traits of a worldwide fish list to our sample to assess its representativeness. Overall, 15.1% of species in the sample were estimated to be threatened with extinction, resulting in a sampled RLI of 0.914 for all species, 0.968 in marine and 0.862 in freshwater ecosystems. Our sample showed fishing as the principal threat for marine species, and pollution by agricultural and forestry effluents for freshwater fishes. The sampled list provides a robust representation for tracking trends in the conservation status of the world’s fishes, including disaggregated sampled indices for marine and freshwater fish. Reassessment and backcasting of this index is urgent to check the achievement of the commitments proposed in global biodiversity targets.

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

A novel technique for aging male African elephants (Loxodonta africana) using craniofacial photogrammetry and geometric morphometrics - Caitlin E. O’Connell-Rodwell; Patrick T. Freeman; Colleen Kinzley; Monica N. Sandri; Jodie L. Berezin; Maggie Wiśniewska; Kelsey Jessup; Timothy C. Rodwell (Mammalian Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Decision Analysis and CO2–Enhanced Oil Recovery Development Strategies - E. D. Attanasi; P. A. Freeman (Natural Resources Research, 2022)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

The kappa-opioid receptor agonist, triazole 1.1, reduces oxycodone self-administration and enhances oxycodone-induced thermal antinociception in male rats - C. Austin Zamarripa; Tanya Pareek; Hayley M. Schrock; Thomas E. Prisinzano; Bruce E. Blough; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2021)

Oklahoma Nathan Shock Aging Center — assessing the basic biology of aging from genetics to protein and function - Holly Van Remmen; Willard M. Freeman; Benjamin F. Miller; Michael Kinter; Jonathan D. Wren; Ann Chiao; Rheal A. Towner; Timothy A. Snider; William E. Sonntag; Arlan Richardson (GeroScience, 2021)

Multiscale Digital Rock Analysis for Complex Rocks - L. C. Ruspini; P. E. Øren; S. Berg; S. Masalmeh; T. Bultreys; C. Taberner; T. Sorop; F. Marcelis; M. Appel; J. Freeman; O. B. Wilson (Transport in Porous Media, 2021)

Modelling potential Pleistocene habitat corridors between Afromontane forest regions - Kaitlin E. Allen; Walter P. Tapondjou; Benedictus Freeman; Jacob C. Cooper; Rafe M. Brown; A. Townsend Peterson (Biodiversity and Conservation, 2021)

Mineralogical and chemical comparison of carbonate from sites selected for cement production with limestone used in commercial operations - Freeman E. D. Senzani; Antoine F. Mulaba-Bafubiandi (Arabian Journal of Geosciences, 2021)

Assessing awareness on biodiversity conservation among Nigerians: the Aichi Biodiversity Target 1 - Emmanuel O. Akindele; Michael C. Ekwemuka; Paul Apeverga; Tajudeen O. Amusa; Samuel Olajuyigbe; Oluwakayode M. Coker; Fatsuma Olaleru; Michelle Fasona; Elizabeth N. Usen; Abubakar S. Ringim; Opeyemi A. Adedoja; Chinedu C. Nsude; et al. (Biodiversity and Conservation, 2021)

The species awareness index as a conservation culturomics metric for public biodiversity awareness - Joseph W. Millard; Richard D. Gregory; Kate E. Jones; Robin Freeman (Conservation Biology, 2021)
Although threats to global biodiversity are well known, slowing current rates of biodiversity loss remains a challenge. The Aichi targets set out 20 goals on which the international community should act to alleviate biodiversity decline, 1 of which (Target 1) aims to raise public awareness of the importance of biodiversity. Although conventional indicators for Target 1 are of low spatial and temporal coverage, conservation culturomics metrics show how biodiversity awareness can be quantified at the global scale. Following methods used for the Living Planet Index, we devised a species awareness index (SAI) to measure change in species awareness based on Wikipedia views. We calculated this index at the page level for 41,197 species listed by the International Union for Conservation of Nature (IUCN) across 10 Wikipedia languages and >2 billion views from 1 July 2015 to 30 March 2020. Bootstrapped indices for the page‐level SAI showed that overall awareness of biodiversity increased marginally over time, although there were differences among taxonomic classes and languages. Among taxonomic classes, overall awareness increased fastest for reptiles and slowest for amphibians. Among languages, overall species awareness increased fastest for Japanese and slowest for Chinese and German users. Although awareness of species as a whole increased and was significantly higher for traded species, from January 2016 through January 2020, change in awareness appeared not to be strongly related to whether the species is traded or is a pollinator. As a data source for public biodiversity awareness, the SAI could be integrated into the Conservation International Biodiversity Engagement Indicator.

Climate‐driven carry‐over effects negatively influence population growth rate in a food‐caching boreal passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Global Change Biology, 2021)
Understanding how events throughout the annual cycle are linked is important for predicting variation in individual fitness, but whether and how carry‐over effects scale up to influence population dynamics is poorly understood. Using 38 years of demographic data from Algonquin Provincial Park, Ontario, and a full annual cycle integrated population model, we examined the influence of environmental conditions and density on the population growth rate of Canada jays ( Perisoreus canadensis ), a resident boreal passerine that relies on perishable cached food for over‐winter survival and late‐winter breeding. Our results demonstrate that fall environmental variables, most notably the number of freeze–thaw events, carried over to influence late‐winter fecundity, which, in turn, was the main vital rate driving population growth. These results are consistent with the hypothesis that warmer and more variable fall conditions accelerate the degradation of perishable stored food that is relied upon for successful reproduction. Future warming during the fall and winter may compromise the viability of cached food that requires consistent subzero temperatures for effective preservation, potentially exacerbating climate‐driven carry‐over effects that impact long‐term population dynamics.

Conscious and unconscious brain responses to food and cocaine cues - Corinde E. Wiers; Jizheng Zhao; Peter Manza; Kristina Murani; Veronica Ramirez; Amna Zehra; Clara Freeman; Kai Yuan; Gene-Jack Wang; Sükrü Barış Demiral; Anna Rose Childress; Dardo Tomasi; et al. (Brain Imaging and Behavior, 2021)

Environmental conditions modulate compensatory effects of site dependence in a food‐caching passerine - Alex O. Sutton; Dan Strickland; Nikole E. Freeman; D. Ryan Norris (Ecology, 2021)
Although density regulates the abundance of most wild animal populations by influencing vital rates, such as fecundity and survival, the mechanisms responsible for generating negative density dependence are unclear for many species. Site dependence occurs when there is preferential filling of high‐quality territories, which results in higher per capita vital rates at low densities because a larger proportion of occupied territories are of high quality. Using 41 yr of territory occupancy and demographic data, we investigated whether site dependence was a mechanism acting to influence fecundity and, by extension, regulate a population of Canada Jays in Algonquin Provincial Park, Ontario, Canada. As predicted by site dependence, the proportion of occupied territories that were of high quality was negatively correlated with population density and periods of vacancy were shorter for high‐quality territories than for low‐quality territories. We also found evidence that per capita fecundity was positively related to the proportion of occupied territories that were of high quality, but only when environmental conditions, which influence the entire population, were otherwise poor for breeding. Our results suggest that site dependence likely plays a role in regulating this population but that environmental conditions can modulate the strength of density dependence.

Climate change impacts on human health at an actionable scale: a state-level assessment of Indiana, USA - G. M. Filippelli; J. L. Freeman; J. Gibson; S. Jay; M. J. Moreno-Madriñán; I. Ogashawara; F. S. Rosenthal; Y. Wang; E. Wells (Climatic Change, 2020)

Potential Environmental Effects of Marine Renewable Energy Development—The State of the Science - Andrea E. Copping; Lenaïg G. Hemery; Dorian M. Overhus; Lysel Garavelli; Mikaela C. Freeman; Jonathan M. Whiting; Alicia M. Gorton; Hayley K. Farr; Deborah J. Rose; Levy G. Tugade (Journal of Marine Science and Engineering, 2020)
Marine renewable energy (MRE) harnesses energy from the ocean and provides a low-carbon sustainable energy source for national grids and remote uses. The international MRE industry is in the early stages of development, focused largely on tidal and riverine turbines, and wave energy converters (WECs), to harness energy from tides, rivers, and waves, respectively. Although MRE supports climate change mitigation, there are concerns that MRE devices and systems could affect portions of the marine and river environments. The greatest concern for tidal and river turbines is the potential for animals to be injured or killed by collision with rotating blades. Other risks associated with MRE device operation include the potential for turbines and WECs to cause disruption from underwater noise emissions, generation of electromagnetic fields, changes in benthic and pelagic habitats, changes in oceanographic processes, and entanglement of large marine animals. The accumulated knowledge of interactions of MRE devices with animals and habitats to date is summarized here, along with a discussion of preferred management methods for encouraging MRE development in an environmentally responsible manner. As there are few devices in the water, understanding is gained largely from examining one to three MRE devices. This information indicates that there will be no significant effects on marine animals and habitats due to underwater noise from MRE devices or emissions of electromagnetic fields from cables, nor changes in benthic and pelagic habitats, or oceanographic systems. Ongoing research to understand potential collision risk of animals with turbine blades still shows significant uncertainty. There has been no significant field research undertaken on entanglement of large animals with mooring lines and cables associated with MRE devices.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Quantification of observable behaviors induced by typical and atypical kappa-opioid receptor agonists in male rhesus monkeys - S. L. Huskinson; D. M. Platt; M. Brasfield; M. E. Follett; T. E. Prisinzano; B. E. Blough; K. B. Freeman (Psychopharmacology, 2020)

Growth Drivers of Bakken Oil Well Productivity - E. D. Attanasi; P. A. Freeman (Natural Resources Research, 2020)
This paper identifies the drivers of the phenomenal growth in productivity in hydraulically fractured horizontal oil wells producing from the middle member of the Bakken Formation in North Dakota. The data show a strong underlying spatial component and somewhat weaker temporal component. Drivers of the spatial component are favorable reservoir conditions. The temporal component of well productivity growth is driven by increasing the number of fracture treatments and by increasing the volume of proppant and injection fluids used on a per fracture treatment basis. Random Forest, a nonparametric modeling procedure often applied in the context of machine learning, is used to identify the relative importance of geologic and well completion factors that have driven the growth in Bakken well productivity. The findings of this study suggest that a significant part of the well productivity increases during the period from 2010 to 2015 has been the result of improved well site selection. For the more recent period, that is, from 2015 through 2017, part of the improved well productivity has resulted from substantial increases in the proppant and injection fluids used per stage and per well.

Pesticide use and risk of Hodgkin lymphoma: results from the North American Pooled Project (NAPP) - Lidija Latifovic; Laura E. Beane Freeman; John J. Spinelli; Manisha Pahwa; Linda Kachuri; Aaron Blair; Kenneth P. Cantor; Shelia Hoar Zahm; Dennis D. Weisenburger; John R. McLaughlin; James A. Dosman; Punam Pahwa; et al. (Cancer Causes & Control, 2020)
Purpose The purpose of this study was to investigate associations between pesticide exposures and risk of Hodgkin lymphoma (HL) using data from the North American Pooled Project (NAPP). Methods Three population-based studies conducted in Kansas, Nebraska, and six Canadian provinces (HL = 507, Controls = 3886) were pooled to estimate odds ratios and 95% confidence intervals for single (never/ever) and multiple (0, 1, 2–4, ≥ 5) pesticides used, duration (years) and, for select pesticides, frequency (days/year) using adjusted logistic regression models. An age-stratified analysis (≤ 40/ > 40 years) was conducted when numbers were sufficient. Results In an analysis of 26 individual pesticides, ever use of terbufos was significantly associated with HL (OR: 2.53, 95% CI 1.04–6.17). In age-stratified analyses, associations were stronger among those ≤ 40 years of age. No significant associations were noted among those > 40 years old; however, HL cases ≤ 40 were three times more likely to report ever using dimethoate (OR: 3.76 95% CI 1.02–33.84) and almost twice as likely to have ever used malathion (OR: 1.86 95% CI 1.00–3.47). Those ≤ 40 years of age reporting use of 5 + organophosphate insecticides had triple the odds of HL (OR: 3.00 95% CI 1.28–7.03). Longer duration of use of 2,4-D, ≥ 6 vs. 0 years, was associated with elevated odds of HL (OR: 2.59 95% CI 1.34–4.97). Conclusion In the NAPP, insecticide use may increase the risk of HL, but results are based on small numbers.

Kappa opioid agonists reduce oxycodone self-administration in male rhesus monkeys - C. Austin Zamarripa; Jennifer E. Naylor; Sally L. Huskinson; E. Andrew Townsend; Thomas E. Prisinzano; Kevin B. Freeman (Psychopharmacology, 2020)

Risk Retirement—Decreasing Uncertainty and Informing Consenting Processes for Marine Renewable Energy Development - Andrea E. Copping; Mikaela C. Freeman; Alicia M. Gorton; Lenaïg G. Hemery (Journal of Marine Science and Engineering, 2020)
Marine renewable energy (MRE) is under development in many coastal nations, adding to the portfolio of low carbon energy sources that power national electricity grids as well as off-grid uses in isolated areas and at sea. Progress in establishing the MRE industry, largely wave and tidal energy, has been slowed in part due to uncertainty about environmental risks of these devices, including harm to marine animals and habitats, and the associated concerns of regulators and stakeholders. A process for risk retirement was developed to organize and apply knowledge in a strategic manner that considered whether specific environmental effects are likely to cause harm. The risk retirement process was tested against two key MRE stressors: effects of underwater noise from operational MRE devices on marine animals, and effects of electromagnetic fields from MRE electrical export cables on marine animals. The effects of installation of MRE devices were not accounted for in this analysis. Applying the risk retirement process could decrease the need for costly investigations of each potential effect at every new MRE project site and help move the industry beyond current barriers.

Raising young with limited resources: supplementation improves body condition and advances fledging of Canada Jays - Nikole E. Freeman; D. Ryan Norris; Alex O. Sutton; Amy E. M. Newman (Ecology, 2020)
Food availability early in life can play a vital role in an individual's development and success, but experimental evidence for the direct effects of food on body condition, physiology, and survival of young animals in the wild is still relatively scarce. Food‐caching Canada Jays ( Perisoreus canadensis ) begin breeding in the late winter and, therefore, rely on either cached food or seemingly limited quantities of fresh food to feed nestlings in the early spring. Using a 2‐yr food supplementation experiment conducted during the nestling period and 40 yr of observational data on food supplemented by the public, we examined whether food quantity during early life influenced the physiology, body condition, timing of fledging, and survival of young Canada Jays in Algonquin Provincial Park, Ontario, Canada . Experimental food supplementation of breeding pairs advanced the fledging date of young by 24% (5.5 d) compared to controls. In 1 yr of the experiment, nestlings raised on experimentally supplemented territories had lower feather corticosterone concentrations and were in higher body condition than controls. Across treatment and control nests, young that successfully fledged had lower concentrations of feather corticosterone and were in higher body condition than those that did not fledge. Based on 40 yr of observational data, nestling body condition was positively related to the degree of food supplementation by park visitors and nestlings in higher body condition were more likely to be observed in the population in the following fall. Our results demonstrate how food availability early in life can have important downstream consequences on metrics related to individual fitness, including first year survival.

A pharmacokinetic-pharmacodynamic assessment of oral antibiotics for pyelonephritis - J. W. S. Cattrall; E. Asín-Prieto; J. Freeman; I. F. Trocóniz; A. Kirby (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Independent QTL underlie resistance to the native pathogen Quambalaria pitereka and the exotic pathogen Austropuccinia psidii in Corymbia - Jakob B. Butler; Brad M. Potts; René E. Vaillancourt; David J. Lee; Geoff S. Pegg; Jules S. Freeman (Tree Genetics & Genomes, 2019)

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Soil organic carbon stability in forests: Distinct effects of tree species identity and traits - Gerrit Angst; Kevin E. Mueller; David M. Eissenstat; Susan Trumbore; Katherine H. Freeman; Sarah E. Hobbie; Jon Chorover; Jacek Oleksyn; Peter B. Reich; Carsten W. Mueller (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations have increased interest in the potential for forest ecosystems and soils to act as carbon (C) sinks. While soil organic C contents often vary with tree species identity, little is known about if, and how, tree species influence the stability of C in soil. Using a 40 year old common garden experiment with replicated plots of eleven temperate tree species, we investigated relationships between soil organic matter (SOM) stability in mineral soils and 17 ecological factors (including tree tissue chemistry, magnitude of organic matter inputs to the soil and their turnover, microbial community descriptors, and soil physicochemical properties). We measured five SOM stability indices, including heterotrophic respiration, C in aggregate occluded particulate organic matter (POM) and mineral associated SOM, and bulk SOM δ 15 N and ∆ 14 C. The stability of SOM varied substantially among tree species, and this variability was independent of the amount of organic C in soils. Thus, when considering forest soils as C sinks, the stability of C stocks must be considered in addition to their size. Further, our results suggest tree species regulate soil C stability via the composition of their tissues, especially roots. Stability of SOM appeared to be greater (as indicated by higher δ 15 N and reduced respiration) beneath species with higher concentrations of nitrogen and lower amounts of acid insoluble compounds in their roots, while SOM stability appeared to be lower (as indicated by higher respiration and lower proportions of C in aggregate occluded POM) beneath species with higher tissue calcium contents. The proportion of C in mineral associated SOM and bulk soil ∆ 14 C, though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change.

Calcite–magnesite solid solutions: using genetic algorithms to understand non-ideality - N. L. Allan; L. Thomas; J. N. Hart; C. L. Freeman; C. E. Mohn (Physics and Chemistry of Minerals, 2019)

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Erythropoietin Upregulates Brain Hemoglobin Expression and Supports Neuronal Mitochondrial Activity - N. K. Singhal; K. Alkhayer; J. Shelestak; R. Clements; E. Freeman; J. McDonough (Molecular Neurobiology, 2018)

Rapid warming is associated with population decline among terrestrial birds and mammals globally - Fiona E. B. Spooner; Richard G. Pearson; Robin Freeman (Global Change Biology, 2018)
Animal populations have undergone substantial declines in recent decades. These declines have occurred alongside rapid, human‐driven environmental change, including climate warming. An association between population declines and environmental change is well established, yet there has been relatively little analysis of the importance of the rates of climate warming and its interaction with conversion to anthropogenic land use in causing population declines. Here we present a global assessment of the impact of rapid climate warming and anthropogenic land use conversion on 987 populations of 481 species of terrestrial birds and mammals since 1950. We collated spatially referenced population trends of at least 5 years’ duration from the Living Planet database and used mixed effects models to assess the association of these trends with observed rates of climate warming, rates of conversion to anthropogenic land use, body mass, and protected area coverage. We found that declines in population abundance for both birds and mammals are greater in areas where mean temperature has increased more rapidly, and that this effect is more pronounced for birds. However, we do not find a strong effect of conversion to anthropogenic land use, body mass, or protected area coverage. Our results identify a link between rapid warming and population declines, thus supporting the notion that rapid climate warming is a global threat to biodiversity.

Global change‐driven effects on dissolved organic matter composition: Implications for food webs of northern lakes - Irena F. Creed; Ann‐Kristin Bergström; Charles G. Trick; Nancy B. Grimm; Dag O. Hessen; Jan Karlsson; Karen A. Kidd; Emma Kritzberg; Diane M. McKnight; Erika C. Freeman; Oscar E. Senar; Agneta Andersson; et al. (Global Change Biology, 2018)
Northern ecosystems are experiencing some of the most dramatic impacts of global change on Earth. Rising temperatures, hydrological intensification, changes in atmospheric acid deposition and associated acidification recovery, and changes in vegetative cover are resulting in fundamental changes in terrestrial–aquatic biogeochemical linkages. The effects of global change are readily observed in alterations in the supply of dissolved organic matter ( DOM )—the messenger between terrestrial and lake ecosystems—with potentially profound effects on the structure and function of lakes. Northern terrestrial ecosystems contain substantial stores of organic matter and filter or funnel DOM , affecting the timing and magnitude of DOM delivery to surface waters. This terrestrial DOM is processed in streams, rivers, and lakes, ultimately shifting its composition, stoichiometry, and bioavailability. Here, we explore the potential consequences of these global change‐driven effects for lake food webs at northern latitudes. Notably, we provide evidence that increased allochthonous DOM supply to lakes is overwhelming increased autochthonous DOM supply that potentially results from earlier ice‐out and a longer growing season. Furthermore, we assess the potential implications of this shift for the nutritional quality of autotrophs in terms of their stoichiometry, fatty acid composition, toxin production, and methylmercury concentration, and therefore, contaminant transfer through the food web. We conclude that global change in northern regions leads not only to reduced primary productivity but also to nutritionally poorer lake food webs, with discernible consequences for the trophic web to fish and humans.

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake - Hannele M. Honkanen; Jessica R. Rodger; Alastair Stephen; Keith Adams; James Freeman; Colin E. Adams (Journal of Fish Biology, 2018)
What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably increased migration time.

Dissociable effects of the kappa opioid receptor agonist nalfurafine on pain/itch-stimulated and pain/itch-depressed behaviors in male rats - Matthew L. Lazenka; Megan J. Moerke; E. Andrew Townsend; Kevin B. Freeman; F. Ivy Carroll; S. Stevens Negus (Psychopharmacology, 2018)

A geographic information system-based method for estimating cancer rates in non-census defined geographical areas - Vincent L. Freeman; Emma E. Boylan; Oksana Pugach; Sara L. Mclafferty; Katherine Y. Tossas-Milligan; Karriem S. Watson; Robert A. Winn (Cancer Causes & Control, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

Illegal Trade of Marine Mammal Bone Exposed: Simple Test Identifies Bones of “Mermaid Ivory” or Steller's Sea Cow (Hydrodamalis gigas) - Lorelei D. Crerar; Elizabeth W. Freeman; Daryl P. Domning; E. Christien Michael Parsons (Frontiers in Marine Science, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Virus disease in wheat predicted to increase with a changing climate - Piotr Trębicki; Narelle Nancarrow; Ellen Cole; Nilsa A. Bosque‐Pérez; Fiona E. Constable; Angela J. Freeman; Brendan Rodoni; Alan L. Yen; Jo E. Luck; Glenn J. Fitzgerald (Global Change Biology, 2015)
Current atmospheric CO 2 levels are about 400 μmol mol −1 and are predicted to rise to 650 μmol mol −1 later this century. Although the positive and negative impacts of CO 2 on plants are well documented, little is known about interactions with pests and diseases. If disease severity increases under future environmental conditions, then it becomes imperative to understand the impacts of pathogens on crop production in order to minimize crop losses and maximize food production . Barley yellow dwarf virus (BYDV) adversely affects the yield and quality of economically important crops including wheat, barley and oats. It is transmitted by numerous aphid species and causes a serious disease of cereal crops worldwide. This study examined the effects of ambient (aCO 2 ; 400 μmol mol −1 ) and elevated CO 2 (eCO 2 ; 650 μmol mol −1 ) on noninfected and BYDV‐infected wheat. Using a RT‐qPCR technique, we measured virus titre from aCO 2 and eCO 2 treatments. BYDV titre increased significantly by 36.8% in leaves of wheat grown under eCO 2 conditions compared to aCO 2 . Plant growth parameters including height, tiller number, leaf area and biomass were generally higher in plants exposed to higher CO 2 levels but increased growth did not explain the increase in BYDV titre in these plants. High virus titre in plants has been shown to have a significant negative effect on plant yield and causes earlier and more pronounced symptom expression increasing the probability of virus spread by insects. The combination of these factors could negatively impact food production in Australia and worldwide under future climate conditions. This is the first quantitative evidence that BYDV titre increases in plants grown under elevated CO 2 levels.

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Association mapping for wood quality and growth traits in Eucalyptus globulus ssp. globulus Labill identifies nine stable marker-trait associations for seven traits - Saravanan Thavamanikumar; Luke J. McManus; Peter K. Ades; Gerd Bossinger; Desmond J. Stackpole; Richard Kerr; Sara Hadjigol; Jules S. Freeman; René E. Vaillancourt; Peng Zhu; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2014)

The Role of Women in Water Management and Conflict Resolution in Marsabit, Kenya - Sarah Yerian; Monique Hennink; Leslie E. Greene; Daniel Kiptugen; Jared Buri; Matthew C. Freeman (Environmental Management, 2014)

Infilled Ditches are Hotspots of Landscape Methane Flux Following Peatland Re-wetting - Mark. D. A. Cooper; Christopher. D. Evans; Piotr Zielinski; Peter. E. Levy; Alan Gray; Mike Peacock; David Norris; Nathalie Fenner; Christopher Freeman (Ecosystems, 2014)

Assessment of the kappa opioid agonist, salvinorin A, as a punisher of drug self-administration in monkeys - Kevin B. Freeman; Jennifer E. Naylor; Thomas E. Prisinzano; William L. Woolverton (Psychopharmacology, 2014)

Open loop optogenetic control of simulated cortical epileptiform activity - Prashanth Selvaraj; Jamie W. Sleigh; Walter J. Freeman; Heidi E. Kirsch; Andrew J. Szeri (Journal of Computational Neuroscience, 2014)

Characterization of Fusarium mangiferae isolates from mango malformation disease in Southern Spain - M. Crespo; E. Arrebola; F. M. Cazorla; M. Maymon; S. Freeman; J. A. Torés; A. de Vicente (European Journal of Plant Pathology, 2014)

Genetic analysis of the near-infrared spectral phenome of a global Eucalyptus species - J. M. O’Reilly-Wapstra; J. S. Freeman; R. Barbour; R. E. Vaillancourt; B. M. Potts (Tree Genetics & Genomes, 2013)

Pesticide use and fatal injury among farmers in the Agricultural Health Study - Jenna K. Waggoner; Paul K. Henneberger; Greg J. Kullman; David M. Umbach; Freya Kamel; Laura E. Beane Freeman; Michael C. R. Alavanja; Dale P. Sandler; Jane A. Hoppin (International Archives of Occupational and Environmental Health, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

Cigarette smoking, alcohol intake, and thyroid cancer risk: a pooled analysis of five prospective studies in the United States - Cari M. Kitahara; Martha S. Linet; Laura E. Beane Freeman; David P. Check; Timothy R. Church; Yikyung Park; Mark P. Purdue; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Transcriptional signatures mediated by acetylation overlap with early-stage Alzheimer’s disease - J. Vadnal; S. Houston; S. Bhatta; E. Freeman; J. McDonough (Experimental Brain Research, 2012)

Comparative epidemiology of CTX-M-14 and CTX-M-15 producing Escherichia coli: Association with distinct demographic groups in the community in New Zealand - J. T. Freeman; D. A. Williamson; H. Heffernan; M. Smith; J. E. Bower; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Methyl bromide exposure and cancer risk in the Agricultural Health Study - Kathryn Hughes Barry; Stella Koutros; Jay H. Lubin; Joseph B. Coble; Francesco Barone-Adesi; Laura E. Beane Freeman; Dale P. Sandler; Jane A. Hoppin; Xiaomei Ma; Tongzhang Zheng; Michael C. R. Alavanja (Cancer Causes & Control, 2012)

Poultry and livestock exposure and cancer risk among farmers in the agricultural health study - Laura E. Beane Freeman; Anneclaire J. DeRoos; Stella Koutros; Aaron Blair; Mary H. Ward; Michael Alavanja; Jane A. Hoppin (Cancer Causes & Control, 2012)

High synteny and colinearity among Eucalyptus genomes revealed by high-density comparative genetic mapping - Corey J. Hudson; Anand R. K. Kullan; Jules S. Freeman; Danielle A. Faria; Dario Grattapaglia; Andrzej Kilian; Alexander A. Myburg; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2012)

Physical activity, diabetes, and thyroid cancer risk: a pooled analysis of five prospective studies - Cari M. Kitahara; Elizabeth A. Platz; Laura E. Beane Freeman; Amanda Black; Ann W. Hsing; Martha S. Linet; Yikyung Park; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Chemical Signals of Elephant Musth: Temporal Aspects of Microbially-Mediated Modifications - Thomas E. Goodwin; Laura J. Broederdorf; Blake A. Burkert; Innocent H. Hirwa; Daniel B. Mark; Zach J. Waldrip; Randall A. Kopper; Mark V. Sutherland; Elizabeth W. Freeman; Julie A. Hollister-Smith; Bruce A. Schulte (Journal of Chemical Ecology, 2012)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Retrospective and prospective model simulations of sea level rise impacts on Gulf of Mexico coastal marshes and forests in Waccasassa Bay, Florida - Laura Geselbracht; Kathleen Freeman; Eugene Kelly; Doria R. Gordon; Francis E. Putz (Climatic Change, 2011)

Quantitative trait loci for foliar terpenes in a global eucalypt species - Julianne M. O’Reilly-Wapstra; Jules S. Freeman; Noel W. Davies; René E. Vaillancourt; Hugh Fitzgerald; Brad M. Potts (Tree Genetics & Genomes, 2011)

Short-Term Impacts of Laurel Wilt on Redbay ( Persea borbonia [L.] Spreng.) in a Mixed Evergreen-Deciduous Forest in Northern Florida - Joshua Shields; Shibu Jose; Johanna Freeman; Milind Bunyan; Gerardo Celis; Donald Hagan; Michael Morgan; E. Corrie Pieterson; Joel Zak (Journal of Forestry, 2011)
We examined the immediate effects of laurel wilt on redbay (Persea borbonia [L.] Spreng.) and stand-level characteristics in a mixed evergreen-deciduous forest at Etoniah Creek State Forest in Florida. Percent mortality of redbay in the overstory, sapling, and seedling layers were 100%, 30.2%, and 1.8%, respectively, in the year after the first signs of infection were observed. The diameter distribution of redbay shifted from a reverse “J” pattern to a distribution where the only remaining living stems were <4-in. dbh. Mortality of redbay also resulted in significant reductions in overstory redbay importance values and stand-level density and basal area. Our results suggest that (1) laurel wilt has a more pronounced effect on overstory redbays than smaller stems and (2) redbay mortality caused by laurel wilt can result in modest but significant changes in stand structure.

Body mass index, agricultural pesticide use, and cancer incidence in the Agricultural Health Study cohort - Gabriella Andreotti; Lifang Hou; Laura E. Beane Freeman; Rajeev Mahajan; Stella Koutros; Joseph Coble; Jay Lubin; Aaron Blair; Jane A. Hoppin; Michael Alavanja (Cancer Causes & Control, 2010)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Training Senior Peer Counselors to Provide Telephone Support for Newly Diagnosed Breast Cancer Survivors - Rebecca Crane-Okada; Evelyn Freeman; Marlena Ross; Holly Kiger; Armando E. Giuliano (Journal of Cancer Education, 2010)

Occupational exposure to terbufos and the incidence of cancer in the Agricultural Health Study - Matthew R. Bonner; Brent A. Williams; Jennifer A. Rusiecki; Aaron Blair; Laura E. Beane Freeman; Jane A. Hoppin; Mustafa Dosemeci; Jay Lubin; Dale P. Sandler; Michael C. R. Alavanja (Cancer Causes & Control, 2010)

Appraising the roles of nutrient availability, global change, and functional traits during the angiosperm rise to dominance - Kevin E. Mueller; Aaron F. Diefendorf; Katherine H. Freeman; David M. Eissenstat (Ecology Letters, 2010)
Ecology Letters (2010) 13: E1–E6 Abstract To explain the rise of angiosperms during the Cretaceous, Berendse & Scheffer ( Ecol. Lett. , 12, 2009, 865) invoke feedbacks between leaf litter, soil nutrients, and growth, overlooking other factors affecting resource acquisition by Cretaceous plants. We evaluate their hypothesis, highlight alternative explanations, and emphasize use of a broader framework for understanding the angiosperm radiation.

Circulating Cytokines as Biomarkers of Alcohol Abuse and Alcoholism - Rajeshwara N. Achur; Willard M. Freeman; Kent E. Vrana (Journal of Neuroimmune Pharmacology, 2010)

QTL influencing growth and wood properties in Eucalyptus globulus - Jules S. Freeman; Simon P. Whittock; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2009)

Microbial activity and diversity during extreme freeze–thaw cycles in periglacial soils, 5400 m elevation, Cordillera Vilcanota, Perú - S. K. Schmidt; D. R. Nemergut; A. E. Miller; K. R. Freeman; A. J. King; A. Seimon (Extremophiles, 2009)

The crystal structure of auracyanin A at 1.85 Å resolution: the structures and functions of auracyanins A and B, two almost identical “blue” copper proteins, in the photosynthetic bacterium Chloroflexus aurantiacus - Mihwa Lee; Melissa C. del Rosario; Hugh H. Harris; Robert E. Blankenship; J. Mitchell Guss; Hans C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 2009)

Population studies and conservation of Jamaica’s endangered swallowtail butterfly Papilio (Pterourus) homerus - Eric Garraway; A. J. A. Bailey; B. E. Freeman; J. R. Parnell; T. C. Emmel (Journal of Insect Conservation, 2008)

Low dose of dopamine may stimulate prolactin secretion by increasing fast potassium currents - Joël Tabak; Natalia Toporikova; Marc E. Freeman; Richard Bertram (Journal of Computational Neuroscience, 2007)

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

Importance of Riparian Forests in Urban Catchments Contingent on Sediment and Hydrologic Regimes - Allison H. Roy; Mary C. Freeman; Byron J. Freeman; Seth J. Wenger; William E. Ensign; Judith L. Meyer (Environmental Management, 2006)

Degradation of benz[a]anthracene by Mycobacterium vanbaalenii strain PYR-1 - Joanna D. Moody; James P. Freeman; Carl E. Cerniglia (Biodegradation, 2005)

Does modafinil activate the locus coeruleus in man? Comparison of modafinil and clonidine on arousal and autonomic functions in human volunteers - R. H. Hou; C. Freeman; R. W. Langley; E. Szabadi; C. M. Bradshaw (Psychopharmacology, 2005)

Admixture and diversity in West African cattle populations - A. R. FREEMAN; C. M. MEGHEN; D. E. MacHUGH; R. T. LOFTUS; M. D. ACHUKWI; A. BADO; B. SAUVEROCHE; D. G. BRADLEY (Molecular Ecology, 2004)
We present a population genetic analysis of microsatellite variation in 16 West African cattle populations. West Africa represents a unique juxtaposition of different climatic and ecological zones in a relatively small geographical area. While more humid coastal regions are inhabited by the tsetse fly, a vector which spreads trypanosomiasis among cattle, the disease is not transmitted in the drier areas outside this zone. This is the most thorough study of genetic diversity in cattle within this area, which contains genetically important trypanotolerant Bos taurus breeds. Genetic relationships among the many breeds are examined and levels of diversity are assessed. Admixture levels were determined using a variety of methods. Ancestry informative or population‐associated alleles (PAAs) were selected using populations from India, the Near East and Europe. Multivariate analysis, the admix program and model‐based Bayesian admixture analysis approaches were also employed. These analyses reveal the direct impact of ecological factors and the profound effect of admixture on the cattle of this region. They also highlight the importance of efforts to prevent further dilution of African taurine breeds by B. indicus cattle.

The use of reference strand‐mediated conformational analysis for the study of cheetah ( Acinonyx jubatus ) feline leucocyte antigen class II DRB polymorphisms - G. J. C. Drake; L. J. Kennedy; H. K. Auty; R. Ryvar; W. E. R. Ollier; A. C. Kitchener; A. R. Freeman; A. D. Radford (Molecular Ecology, 2004)
There is now considerable evidence to suggest the cheetah ( Acinonyx jubatus ) has limited genetic diversity. However, the extent of this and its significance to the fitness of the cheetah population, both in the wild and captivity, is the subject of some debate. This reflects the difficulty associated with establishing a direct link between low variability at biologically significant loci and deleterious aspects of phenotype in this, and other, species. Attempts to study one such region, the feline leucocyte antigen (FLA), are hampered by a general reliance on cloning and sequencing which is expensive, labour‐intensive, subject to PCR artefact and always likely to underestimate true variability. In this study we have applied reference strand‐mediated conformational analysis (RSCA) to determine the FLA–DRB phenotypes of 25 cheetahs. This technique was rapid, repeatable and less prone to polymerase chain reaction (PCR)‐induced sequence artefacts associated with cloning. Individual cheetahs were shown to have up to three FLA–DRB genes. A total of five alleles were identified (DRB*ha14–17 and DRB*gd01) distributed among four genotypes. Fifteen cheetahs were DRB*ha14/ha15/ha16/ha17, three were DRB*ha15/ha16/ha17, six were DRB*ha14/ha16/ha17 and one was DRB*ha14/ha15/ha16/ha17/gd01. Sequence analysis of DRB*gd01 suggested it was a recombinant of DRB*ha16 and DRB*ha17. Generation of new alleles is difficult to document, and the clear demonstration of such an event is unusual. This study confirms further the limited genetic variability of the cheetah at a biologically significant region. RSCA will facilitate large‐scale studies that will be needed to correlate genetic diversity at such loci with population fitness in the cheetah and other species.

Microsatellite primers indicate the presence of asexual populations ofVenturia inaequalis in coastal Israeli apple orchards - Eric W. A. Boehm; S. Freeman; E. Shabi; T. J. Michailides (Phytoparasitica, 2003)

A thin-film electrochemical study of the "blue" copper proteins, auracyanin A and auracyanin B, from the photosynthetic bacterium Chloroflexus aurantiacus: the reduction potential as a function of pH - Melissa B. Rooney; Michael J. Honeychurch; Fabiola M. Selvaraj; Robert E. Blankenship; Alan M. Bond; Hans C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 2003)

Evidence that channel catfish, Ictalurus punctatus (Rafinesque), mortality is not linked to ingestion of the hepatotoxin microcystin‐LR - G S Snyder; A E Goodwin; D W Freeman (Journal of Fish Diseases, 2002)
Catfish farms located in the south‐eastern USA using brackish (3–5 g NaCl L −1 ) well water experience sporadic fish kills sometimes with high mortality. An investigation of three catastrophic losses occurring in this region identified no involvement of infectious diseases or traditional water quality problems, including oxygen, ammonia or nitrite. The high mortality and time course of the problem was indicative of exposure to a toxin. Attempts by other workers to explain the cause of this unique syndrome (high chloride associated toxicosis of catfish, HCTC), suggested that the losses might be because of microcystin‐producing blooms of Microcystis aeruginosa , but our investigations failed to support this conclusion . We found that (1) the liver histology of catfish experimentally exposed to pure microcystin‐LR is very different from that of catfish sampled during outbreaks of HCTC; (2) measurements of microcystin‐LR concentrations in the three cases were far lower than the concentration required to kill catfish by experimental immersion; (3) the HCTC toxin appears to have a short half‐life, whereas microcystin‐LR does not; (4) experimental gavage of catfish with massive amounts of microcystin‐LR does not cause the acute mortality typical of HCTC; (5) outbreaks of HCTC appear to be associated with heavy blooms of Anacystis marina , a halophytic cyanobacteria, not with blooms of M. aeruginosa .

Radiation hybrid mapping of 70 rat genes from a data set of differentially expressed genes - Caroline A. Wallace; Saira Ali; Anne M. Glazier; Penny J. Norsworthy; Danilo C. Carlos; James Scott; Tom C. Freeman; Lawrence W. Stanton; Anne E. Kwitek; Timothy J. Aitman (Mammalian Genome, 2002)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Sexual selection and the geography of Plasmodium infection in Savannah sparrows (Passerculus sandwichensis) - Corey R. Freeman-Gallant; Kathleen D. O’Connor; Megan E. Breuer (Oecologia, 2001)

Administration of FGF-1 through transfected cells alleviates MPTP toxicity in mice - Robert N. Mclay; Scott M. Freeman; James E. Zadina (Neurotoxicity Research, 2001)

Survival of introduced Tuber melanosyorum at two sites in Israel as measured by occurrence of mycorrhizas - V. Kagan-Zur; S. Freeman; Y. Luzzati; Nurit Roth-Bejerano; E. Shabi (Plant and Soil, 2001)

Narrow hybrid zone between two subspecies of big sagebrush (Artemisia tridentata: Asteraceae) - John H. Graham; E. Durant McArthur; D. Carl Freeman (Oecologia, 2001)

Sequence Heteroplasmy of D-Loop and rRNA Coding Regions in Mitochondrial DNA from Holstein Cows of Independent Maternal Lineages - Jianming Wu; Renotta K. Smith; A. E. Freeman; Donald C. Beitz; Ben T. McDaniel; Gary L. Lindberg (Biochemical Genetics, 2000)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Human HPA Endoglycosidase Heparanase Map Position 4q21.3 - E. Baker; J. Crawford; G.R. Sutherland; C. Freeman; C.R. Parish; M.D. Hulett (Chromosome Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Spectroscopic identification of a dinuclear metal centre in manganese(II)-activated aminopeptidase P from Escherichia coli: implications for human prolidase - Lianbo Zhang; Maxwell J. Crossley; Nicholas E. Dixon; Paul J. Ellis; Megan L. Fisher; Glenn F. King; Penelope E. Lilley; Dugald MacLachlan; Ronald J. Pace; H. C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Inter-strain comparison by pyrolysis mass spectrometry of Staphylococcus aureus isolates associated with nosocomial infection - P.R. Sisson; E. Nagy; Z. Kòczián; E. Veszelovsky; R. Freeman (Antonie van Leeuwenhoek, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Sexual specialization and inbreeding avoidance in the evolution of dioecy - D. Carl Freeman; Jon Lovett Doust; Ali El-Keblawy; Kathleen J. Miglia; E. Durant McArthur (The Botanical Review, 1997)

Cohesive sediment transport on an inter-tidal zone under combined wave-tidal flow - D. P. Freeman; L. E. Coates; M. C. Ockenden; W. Roberts; J. R. West (Aquatic Ecology, 1994)

Dipeptidase-C inDrosophila melanogaster: Genetic, ontogenetic, and tissue-specific variation - Kazuo Hiraizumi; Catherine L. Hourani; Mary C. Zambarano; James E. Freeman; Karen D. Mathes (Biochemical Genetics, 1992)

Dipeptidase-C inDrosophila melanogaster: Genetic, ontogenetic, and tissue-specific variation - Kazuo Hiraizumi; Catherine L. Hourani; Mary C. Zambarano; James E. Freeman; Karen D. Mathes (Biochemical Genetics, 1992)

Biodegradation of 1-nitropyrene - Michael A. Heitkamp; James P. Freeman; Dwight W. Miller; Carl E. Cerniglia (Archives of Microbiology, 1991)

Stereoselective formation of a K-region dihydrodiol from phenanthrene by Streptomyces flavovirens - John B. Sutherland; James P. Freeman; Allison L. Selby; Peter P. Fu; Dwight W. Miller; Carl E. Cerniglia (Archives of Microbiology, 1990)

Identification of metabolites from degradation of naphthalene by a Mycobacterium sp. - Ingrid Kelley; James P. Freeman; Carl E. Cerniglia (Biodegradation, 1990)

Evidence for an arene oxide-NIH shift pathway in the transformation of naphthalene to 1-naphthol by Bacillus cereus - Carl E. Cerniglia; J. P. Freeman; Frederick E. Evans (Archives of Microbiology, 1984)

Metabolism and toxicity of 1- and 2-methylnaphthalene and their derivatives in cyanobacteria - Carl E. Cerniglia; J. P. Freeman; James R. Althaus; Chase van Baalen (Archives of Microbiology, 1983)

A histopathological examination of, and analysis for polychlorinated hydrocarbons in, inshore Atlantic cod (Gadus morhua) - H. C. Freeman; G. B. Sangalang; J. F. Uthe; E. T. Garside; P. G. Daye (Archives of Environmental Contamination and Toxicology, 1983)

Parental investment and its ecological consequences in the solitary wasp Sceliphron assimile (Dahlbom) (Sphecidae) - B. E. Freeman (Behavioral Ecology and Sociobiology, 1981)

Biotransformation and toxicity of aniline and aniline derivatives in cyanobacteria - Carl E. Cerniglia; J. P. Freeman; Chase Van Baalen (Archives of Microbiology, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

“Errata” in vol. IV, No. 4, April, 1927 - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)

Effect of fertilizer on potato tubers - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)

Physiological and storage problems number - H. S. Yohe; Wm. Stuart; C. O. Appleman; John Bushnell; Julian A. Dimock; J. T. Rosa; Earl S. Johnston; E. P. Miller; Freeman Weiss (American Journal of Potato Research, 1925)